Social Network and Demographic Factors on Quality of Life among Youths in Ibadan Greater Municipality - David E. Okurame; Bolanle S. Faseyitan; Emmanuel E. Uye (Citakonsultindo, 2025)
Quality of life among Nigerian youths has continued to be an issue of concern due to the state of the country's economic situations. Studies have examined quality of life among youths using different factors with varied results. Therefore, this study investigated social network and demographic factors on quality of life among youths in Ibadan, Nigeria. Cross-sectional survey design was adopted while a simple random sampling method was used to select five Local Government Areas in Ibadan Greater Municipality (IGM). Data were collected from 355 participants using validated scales and analyzed using multiple regression analysis and independent samples t-test statistics. Two hypotheses were tested and accepted at p =.001 level of significance. The result revealed that social networks significantly influence quality of life among youths in IGM [t (353) =5.60, p =.001]. The result further showed that demographic factors of age, gender and educational status jointly predicted quality of life among youths in IGM [R2 =. 062, F(3, 350) = 4.578, p = .001]. However, it was only educational status that independently predicted quality of life among study participants (β = -234, t= -4.478, p =.001). It is concluded that social networks and demographic factors of educational status are strong contributors to quality of life among youths in IGM. The study recommended that government and other stakeholders should empower youths with skills and career plans to improve their quality of life.